Preparation method of fuel cell metal bipolar plate composite coating
By depositing a composite coating method of metal base layer, metal nitrogen/carbide transition layer and multi-arc ion plating amorphous carbon surface layer on the fuel cell metal bipolar plate, the problem of fragility and easy peeling and contamination of the surface of the carbon-based coating is solved, and the effect of improving corrosion resistance and conductivity is achieved, and environmental pollution is reduced.
Patent Information
- Application Number
- CN202411894007.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art When preparing the carbon-based coating of fuel cell metal bipolar plates, the surface is easily fragile and peeling, and the problem of contamination is not effectively solved.
A composite coating preparation method is adopted in which the metal base layer, the metal nitrogen/carbide transition layer and the amorphous carbon surface layer formed by multi-arc ion plating are sequentially deposited on the metal bipolar plate substrate.
This method not only improves the corrosion resistance and conductivity of the bipolar plate and extends the service life of the fuel cell, but also reduces the emission of harmful gases and reduces the pollution to the environment by performing the core steps in a vacuum environment.
Smart Images

Figure CN119800294A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fuel cell manufacturing, and in particular to a method for preparing a composite coating of a fuel cell metal bipolar plate. Background Art
[0002] As a clean energy, hydrogen energy has received extensive attention. How to use hydrogen energy efficiently and safely has become a research hotspot in the field of new energy. The hydrogen fuel power system composed of hydrogen energy and fuel cells has great advantages in terms of high efficiency, high power density, low noise, energy saving and environmental protection. However, the service life of hydrogen fuel cells has always been a hot topic of research. Among them, the bipolar plate is a key component that affects the service life of hydrogen fuel cells. In the high temperature, strong acid and high potential service environment of the fuel cell, it is very easy to produce surface corrosion and oxidation, the conductivity decreases, the interface contact resistance increases, and then the fuel cell working efficiency and service life decay. Therefore, fuel cells have high requirements for the conductivity and corrosion resistance of metal bipolar plates. In response to the above problems, a common method is to coat the surface of the metal bipolar plate to meet the performance requirements of high conductivity and corrosion resistance at the same time. Studies have shown that depositing metal-based coatings and carbon-based coatings on the surface of metal bipolar plates is an effective method to improve the performance of metal bipolar plates. However, precious metal coatings are expensive, conventional metal coatings have low corrosion resistance, and the surface of single carbon-based coatings is fragile and easy to peel off, which limits the performance of metal bipolar plates. Therefore, it is necessary to improve the performance of metal bipolar plates and reduce the cost of coating preparation through coating structure and composition design.
[0003] Patent document CN109037723B discloses a graphite microcrystalline carbon coating and application for metal bipolar plates of fuel cells. The coating is coated on the surface of the metal bipolar plate. The graphite microcrystalline carbon coating is a graphite-like coating, which contains 5wt%-50wt% of graphite microcrystals and has good compactness. Based on conventional magnetron sputtering technology, the coating changes the energy of deposited particles by changing the target sputtering power supply, sputtering magnetic field strength, coating deposition temperature and other methods, thereby changing the structure of the carbon coating to prepare a highly conductive, corrosion-resistant and stable carbon coating. The problem that the existing preparation method prepares a carbon-based coating with a fragile surface that is easy to peel off and causes pollution is not solved.
[0004] In the patent document CN101640276B, an amorphous carbon coating for a bipolar plate of a fuel cell is disclosed, which relates to a flow field plate for fuel cell application, including a metal plate, on at least a portion of which an amorphous carbon layer is deposited. The amorphous carbon layer includes a hydrophilic activated surface; the metal plate has a first surface and a second surface, the first surface defines a plurality of channels for guiding the flow of a first gaseous composition and an amorphous carbon layer disposed on at least a portion of the metal plate, the amorphous carbon layer having a carbon layer surface with a contact angle of less than 30 degrees, and the problem that the existing preparation method prepares a carbon-based coating with a fragile surface that is easy to peel off and causes pollution is not solved.
[0005] In summary, the above two existing patents do not solve the problem that the carbon-based coating surface prepared by the existing preparation method is fragile and easy to peel off and causes pollution. Summary of the invention
[0006] Based on the above technical problems, the present invention proposes a method for preparing a composite coating for a fuel cell metal bipolar plate, which solves the problem that the surface of the carbon-based coating prepared by the existing preparation method is fragile and easy to peel off, causing pollution.
[0007] To achieve the above object, the present invention provides a method for preparing a composite coating of a fuel cell metal bipolar plate.
[0008] A method for preparing a composite coating of a fuel cell metal bipolar plate, comprising:
[0009] S1: pre-treat and clean the substrate;
[0010] S2: depositing a metal primer layer and a transition layer on the surface of the substrate in sequence;
[0011] S3: depositing an amorphous carbon surface layer on the surface of the transition layer by multi-arc ion plating.
[0012] Furthermore, the step S1 includes:
[0013] After the pretreatment of the substrate is completed, the substrate is placed in a vacuum chamber for plasma cleaning.
[0014] Furthermore, the preprocessing includes:
[0015] Alkaline cleaning, rust removal and pure water rinsing.
[0016] Further, the alkali washing comprises:
[0017] The substrate is immersed in a KOH solution with a mass percentage of 10%-15% and a temperature of 70° C.-90° C., and the substrate is ultrasonically cleaned for 5 min-20 min.
[0018] Furthermore, the rust removal comprises:
[0019] The substrate is immersed in a H2SO4 solution with a mass percentage of 10%-15% and a temperature of 70°C-90°C, and the substrate is ultrasonically cleaned for 5 minutes to 20 minutes.
[0020] Further, the pure water rinsing comprises:
[0021] The substrate is placed in a cleaning tank and rinsed with ultrapure water for 5 minutes to 20 minutes.
[0022] Furthermore, it also includes:
[0023] The substrate rinsed with pure water is taken out, and the surface of the substrate is blown dry with compressed air at a temperature of 15° C.-30° C. and a pressure of 0.4 MPa-0.9 MPa.
[0024] Furthermore, the step S1 further includes:
[0025] After the substrate is subjected to any one of the steps of alkali washing, rust removal and pure water rinsing in the pretreatment, the surface of the substrate is sprayed and rinsed with pure water.
[0026] Further, the plasma cleaning comprises:
[0027] The substrate is placed in the vacuum chamber, argon gas is introduced into the vacuum chamber, the pressure inside the vacuum chamber is 0.1Pa-1Pa, the temperature is 100°C-200°C, the applied voltage is -500V-800V, and the plasma cleaning time is 5min-30min.
[0028] Furthermore, the step S2 includes:
[0029] A metal base layer is deposited on the surface of the substrate by magnetron sputtering. After the metal base layer is completed, a transition layer is continuously deposited on the surface of the metal base layer by magnetron sputtering.
[0030] Furthermore, the step S2 includes:
[0031] The material of the metal primer layer includes titanium, vanadium, chromium, zirconium, niobium, molybdenum or tantalum.
[0032] Furthermore, the step of depositing a metal primer layer on the surface of the substrate by magnetron sputtering comprises:
[0033] Argon gas is introduced into the vacuum chamber, the flow rate of argon gas is 200sccm-300sccm, the pressure is 0.1Pa-1Pa, the temperature is 100℃-200℃, the applied current is 2A-10A, and the deposition time is 10min-60min, until the thickness of the metal base layer reaches 97nm-155nm.
[0034] Furthermore, the step S2 includes:
[0035] The material of the transition layer includes titanium carbide, titanium nitride, titanium carbide nitride, niobium carbide or chromium carbide.
[0036] Further, the step of depositing a transition layer on the surface of the metal base layer by magnetron sputtering comprises:
[0037] Argon and nitrogen are introduced into the vacuum chamber, the argon flow rate is 180sccm-280sccm, the pressure is 0.1Pa-1Pa, the temperature is 100℃-200℃, the applied current is 2A-10A, and the deposition time is 10min-60min, until the thickness of the transition layer reaches 48nm-103nm.
[0038] Furthermore, the step S3 includes:
[0039] The surface of the transition layer is deposited multiple times by multi-arc ion plating until the amorphous carbon surface layer reaches a required thickness.
[0040] Furthermore, the step S3 includes:
[0041] The material of the amorphous carbon surface layer is amorphous carbon.
[0042] Furthermore, the process of performing multiple cycles of deposition on the surface of the transition layer by multi-arc ion plating until the amorphous carbon surface layer reaches a required thickness comprises:
[0043] Argon gas is introduced into the vacuum chamber, the flow rate of argon gas is 50sccm-100sccm, the pressure is 0.1Pa-1Pa, the temperature is 100℃-150℃, the deposition time is 10min-20min, and the deposition is cycled 2-4 times until the thickness of the amorphous carbon surface layer reaches 147nm-255nm.
[0044] Based on the above technical solution, the present invention has at least the following beneficial effects:
[0045] 1. The present invention proposes a method for preparing a composite coating of a metal bipolar plate of a fuel cell, wherein a metal base layer, a metal nitrogen / carbide transition layer and an amorphous carbon surface layer are sequentially deposited on a metal bipolar plate substrate to form a composite coating structure. This structure not only improves the corrosion resistance of the bipolar plate, but also enhances its conductivity. The synergistic effect of the metal base layer, the transition layer and the amorphous carbon surface layer ensures that the bipolar plate can maintain low contact resistance and high conductivity in the high temperature, strong acid and high potential environment of the fuel cell, thereby improving the working efficiency and response speed of the battery; an amorphous carbon surface layer with strong adhesion, not easy to fall off, uniform thickness and low porosity is formed by multi-arc ion plating technology, and the composition and structure of the amorphous carbon surface layer are precisely controlled to achieve fine regulation of the performance of the amorphous carbon surface layer.
[0046] 2. The present invention proposes a method for preparing a composite coating of a fuel cell metal bipolar plate. The multi-arc ion plating technology is used to form a high-density and high-strength amorphous carbon surface layer on the surface of the metal bipolar plate, which significantly improves the corrosion resistance of the bipolar plate. By accurately controlling the processing parameters of the multi-arc ion plating, an amorphous carbon surface layer with fine grains and few defects can be prepared on the surface of the bipolar plate, effectively reducing the corrosion current density and extending the service life of the fuel cell. At the same time, the technology ensures good bonding between the amorphous carbon surface layer and the substrate, maintaining the high conductivity of the bipolar plate, which is crucial to maintaining the efficient operation of the fuel cell.
[0047] 3. The present invention proposes a method for preparing a composite coating for a fuel cell metal bipolar plate. Through the optimization design of the coating structure, the metal bipolar plate obtained by the preparation method exhibits excellent durability in a fuel cell environment; the presence of the metal nitrogen / carbide transition layer enhances the bonding force between the substrate and the surface layer, effectively preventing the coating from peeling off and corrosion; the introduction of the amorphous carbon surface layer further improves the stability of the coating, reduces the performance degradation caused by corrosion during long-term use, and enables it to have excellent corrosion resistance and long-term stability.
[0048] 4. The present invention proposes a method for preparing a composite coating of a metal bipolar plate of a fuel cell. The core steps of the preparation method are all carried out in a vacuum environment, which significantly reduces the emission of harmful gases. The vacuum environment effectively avoids the harmful chemical reactions that may occur when oxygen and other gases in the atmosphere come into contact with high-temperature materials, thereby reducing pollution to the environment; in a vacuum environment, the evaporation and deposition efficiency of the material is improved, which means that less material can be used to achieve the same coating effect. This efficiency improvement not only reduces the cost of raw materials, but also reduces the generation of waste, further reducing the impact on the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0050] Figure 1 A flow chart showing a method for preparing a composite coating of a fuel cell metal bipolar plate according to an embodiment; DETAILED DESCRIPTION
[0051] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0052] The present invention is further described in detail below in conjunction with specific embodiments, and these embodiments cannot be understood as limiting the scope of protection claimed by the present invention. The term "including" when used indicates the existence of a feature, but does not exclude the existence or addition of one or more other features; the orientation or position relationship indicated by the terms "lateral", "upper", "lower", "front", "rear", "left", "right", "top", "bottom", "inside", "outside", etc. is based on the orientation or position relationship shown in the drawings, which is only for the convenience of description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention; in addition, the terms "first" and "second" are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance.
[0053] In the description, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be directly connected, or indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances. In addition, in the description of the present invention, unless otherwise specified, "plurality" means two or more.
[0054] Example
[0055] The problem that the carbon-based coating prepared by the existing preparation method is fragile, easy to peel off and causes pollution has not been solved. The present invention proposes a preparation method for a composite coating of a fuel cell metal bipolar plate.
[0056] Example 1
[0057] like Figure 1 A flow chart of a method for preparing a composite coating of a fuel cell metal bipolar plate of the present invention is shown in FIG. 1 , and the process mainly includes the following steps:
[0058] S1: The thickness of the substrate is 0.075 mm. After filling the cleaning tank with a KOH solution with a mass percentage of 10% and a temperature of 70°C, the substrate is placed in the cleaning tank and ultrasonically cleaned for 5 minutes. After cleaning, the substrate is taken out and suspended in an empty cleaning tank and sprayed with pure water. After filling the cleaning tank with a H2SO4 solution with a mass percentage of 10% and a temperature of 70°C, the substrate is placed in the cleaning tank and ultrasonically cleaned for 5 minutes. After cleaning, the substrate is taken out and suspended in an empty cleaning tank. The method comprises the following steps: placing the substrate in an empty cleaning tank and spraying it with pure water; filling the cleaning tank with ultrapure water, rinsing the substrate for 5 minutes, discharging the ultrapure water after rinsing and spraying it with pure water, and drying the surface of the substrate with compressed air at a temperature of 25°C and a pressure of 0.4MPa; placing the substrate in a vacuum chamber, evacuating the vacuum chamber, and then introducing argon gas so that the temperature in the vacuum chamber is 100°C and the pressure is 0.1Pa, applying a bias voltage of -500V, and the plasma cleaning time is 5 minutes.
[0059] S2: A metal base layer is deposited on the surface of the substrate by high-power pulsed magnetron sputtering, and the material of the metal base layer is derived from a titanium target. Argon gas is introduced into a vacuum chamber, and the flow rate of argon gas is 200 sccm, the pressure is 0.1 Pa, the temperature is 100°C, the applied current is 2A, and the deposition time is 10 minutes, until the thickness of the metal base layer reaches about 100nm; a transition layer is deposited on the surface of the substrate by high-power pulsed magnetron sputtering, and the material of the transition layer is derived from a titanium target and a carbon target. Argon gas is introduced into a vacuum chamber, and the flow rate of argon gas is 180 sccm, the pressure is 0.1 Pa, the temperature is 100°C, the applied current is 2A, and the deposition time is 10 minutes, until the thickness of the transition layer reaches about 50nm.
[0060] S3: The flow rate of argon gas in the vacuum chamber is maintained at 50 sccm, the pressure in the vacuum chamber is 0.1 Pa, and the temperature is 100°C. An amorphous carbon surface layer is deposited on the surface of the transition layer by multi-arc ion plating. The material source of the amorphous carbon surface layer is a carbon target. The deposition time is 10 minutes. The deposition is repeated twice until the thickness of the amorphous carbon surface layer reaches about 150 nm.
[0061] Example 2
[0062] S1: Preferably, the thickness of the substrate is 0.075 mm. After filling the cleaning tank with a KOH solution with a mass percentage of 13% and a temperature of 80°C, the substrate is placed in the cleaning tank and ultrasonically cleaned for 5 minutes. After the cleaning is completed, the substrate is taken out and suspended on an empty cleaning tank and sprayed with pure water. After filling the cleaning tank with a H2SO4 solution with a mass percentage of 13% and a temperature of 80°C, the substrate is placed in the cleaning tank and ultrasonically cleaned for 5 minutes. After the cleaning is completed, the substrate is taken out The substrate was suspended on an empty cleaning tank and sprayed with pure water; the cleaning tank was filled with ultrapure water, and the substrate was rinsed for 5 minutes. After rinsing, the ultrapure water was discharged and sprayed with pure water, and the surface of the substrate was blown dry with compressed air at a temperature of 25°C and a pressure of 0.4MPa; the substrate was placed in a vacuum chamber, and the vacuum chamber was evacuated, and argon gas was then introduced to make the temperature in the vacuum chamber 100°C, the pressure 0.6Pa, the bias voltage applied was -350V, and the plasma cleaning time was 15min.
[0063] S2: depositing a metal base layer on the surface of the substrate by high-power pulsed magnetron sputtering, preferably the material of the metal base layer is derived from a titanium target, and argon gas is introduced into a vacuum chamber, the flow rate of argon gas is 260sccm, the pressure is 0.5Pa, the temperature is 150°C, the applied current is 6A, and the deposition time is 30min, until the thickness of the metal base layer reaches about 125nm; depositing a transition layer on the surface of the substrate by high-power pulsed magnetron sputtering, the material of the transition layer is derived from a titanium target and a carbon target, and argon gas is introduced into a vacuum chamber, the flow rate of argon gas is 260sccm, the pressure is 0.5Pa, the temperature is 150°C, the applied current is 6A, and the deposition time is 30min, until the thickness of the transition layer reaches about 75nm.
[0064] S3: Preferably, the flow rate of argon gas in the vacuum chamber is maintained at 75 sccm, the pressure in the vacuum chamber is 0.5 Pa, the temperature is 150°C, and an amorphous carbon surface layer is deposited on the surface of the transition layer by multi-arc ion plating. The material source of the amorphous carbon surface layer is a carbon target. The deposition time is 15 minutes, and the deposition is repeated 3 times until the thickness of the amorphous carbon surface layer reaches about 200 nm.
[0065] Example 3
[0066] S1: The thickness of the substrate is 0.075 mm. After filling the cleaning tank with a KOH solution with a mass percentage of 15% and a temperature of 90°C, the substrate is placed in the cleaning tank and ultrasonically cleaned for 5 minutes. After cleaning, the substrate is taken out and hung on an empty cleaning tank and sprayed with pure water. After filling the cleaning tank with a H2SO4 solution with a mass percentage of 15% and a temperature of 90°C, the substrate is placed in the cleaning tank and ultrasonically cleaned for 20 minutes. After cleaning, the substrate is taken out The substrate was suspended on an empty cleaning tank and sprayed with pure water; the cleaning tank was filled with ultrapure water, and the substrate was rinsed for 20 minutes. After rinsing, the ultrapure water was discharged and sprayed with pure water, and the surface of the substrate was blown dry with compressed air at a temperature of 25°C and a pressure of 0.9MPa; the substrate was placed in a vacuum chamber, and the vacuum chamber was evacuated, and argon gas was then introduced to make the temperature in the vacuum chamber 100°C, the pressure 1Pa, the applied voltage 800V, and the plasma cleaning time 30min.
[0067] S2: A metal base layer is deposited on the surface of the substrate by high-power pulse magnetron sputtering, and the material of the metal base layer is derived from a titanium target. Argon gas is introduced into a vacuum chamber, and the flow rate of argon gas is 300sccm, the pressure is 1Pa, the temperature is 200°C, the applied current is 10A, and the deposition time is 60min, until the thickness of the metal base layer reaches about 150nm; a transition layer is deposited on the surface of the substrate by high-power pulse magnetron sputtering, and the material of the transition layer is derived from a titanium target and a carbon target. Argon gas is introduced into a vacuum chamber, and the flow rate of argon gas is 280sccm, the pressure is 1Pa, the temperature is 200°C, the applied current is 10A, and the deposition time is 60min, until the thickness of the transition layer reaches about 100nm.
[0068] S3: The flow rate of argon gas in the vacuum chamber is maintained at 100 sccm, the pressure in the vacuum chamber is 1 Pa, and the temperature is 150°C. An amorphous carbon surface layer is deposited on the surface of the transition layer by multi-arc ion plating. The material source of the amorphous carbon surface layer is a carbon target. The deposition time is 20 minutes. The deposition is repeated 4 times until the thickness of the amorphous carbon surface layer reaches about 250 nm.
[0069] As shown in Table 1 below, the fuel cell metal bipolar plate composite coating data table of Example 1, Example 2 and Example 3, the composite coating is prepared by controlling different pressures, current intensities, deposition times and coating thicknesses, and the contact resistance and corrosion current density results of different composite coatings are compared in Table 1.
[0070] Table 1 Fuel cell metal bipolar plate composite coating data table
[0071]
[0072] Comparative Example 1
[0073] This comparative case 1 is used as a comparative example of Example 2. Steps S1 and S2 are exactly the same as those of Example 2. In step S3, the DC magnetron sputtering technology is selected as the coating process, and other parameters are the same as those of Example 2.
[0074] Performance comparison:
[0075] The corrosion resistance of the sample was measured by a three-electrode electrochemical test system. The solution was H2SO4+0.1ppmHF solution (pH=3) and the solution temperature was 80°C. The corrosion current density of the sample in Example 2 was 0.043μA / cm at a standard working voltage of 0.84V. 2 The corrosion current density of the sample in comparative example 1 is 0.059 μA / cm at a standard working voltage of 0.84 V. 2 The corrosion current density of Example 2 is significantly lower than that of Comparative Example 1, indicating that the coating prepared in the embodiment of the present invention has better corrosion resistance.
[0076] An assembly preload of 1.5 MPa was applied to the sample surface, and a contact resistance test was performed. The contact resistance of the coating in Example 2 was 2.33 mΩ·cm 2 The contact resistance of the coating in Comparative Example 1 is 3.41 mΩ·cm 2 The contact resistance of the coating in Example 2 is lower than that in Comparative Example 1, which proves that Example 2 has better conductivity.
[0077] In summary, it can be seen from the above description that the above embodiments of the present invention achieve the following technical effects:
[0078] 1. The present invention proposes a method for preparing a composite coating of a metal bipolar plate of a fuel cell, wherein a composite coating structure is formed by sequentially depositing a metal base layer, a metal nitrogen / carbide transition layer and an amorphous carbon surface layer on a metal bipolar plate substrate. This structure not only improves the corrosion resistance of the bipolar plate, but also reduces its contact resistance. The synergistic effect of the metal base layer, the transition layer and the amorphous carbon surface layer ensures that the bipolar plate can maintain low contact resistance and high conductivity in the high temperature, strong acid and high potential environment of the fuel cell, thereby improving the working efficiency and response speed of the battery; an amorphous carbon surface layer with strong adhesion, not easy to fall off, uniform thickness and low porosity is formed by multi-arc ion plating technology, and the composition and structure of the amorphous carbon surface layer are precisely controlled to achieve fine regulation of the performance of the amorphous carbon surface layer.
[0079] 2. The present invention proposes a method for preparing a composite coating of a fuel cell metal bipolar plate. The multi-arc ion plating technology is used to form a high-density and high-strength amorphous carbon surface layer on the surface of the metal bipolar plate, which significantly improves the corrosion resistance of the bipolar plate. By accurately controlling the processing parameters of the multi-arc ion plating, an amorphous carbon surface layer with fine grains and few defects can be prepared on the surface of the bipolar plate, effectively reducing the corrosion current density and extending the service life of the fuel cell. At the same time, the technology ensures good bonding between the amorphous carbon surface layer and the substrate, maintaining the high conductivity of the bipolar plate, which is crucial to maintaining the efficient operation of the fuel cell.
[0080] 3. The present invention proposes a method for preparing a composite coating for a fuel cell metal bipolar plate. Through the optimization design of the coating structure, the metal bipolar plate obtained by the preparation method exhibits excellent durability in a fuel cell environment; the presence of the metal nitrogen / carbide transition layer enhances the bonding force between the substrate and the surface layer, effectively preventing the coating from peeling off and corrosion; the introduction of the amorphous carbon surface layer further improves the stability of the coating, reduces the performance degradation caused by corrosion during long-term use, and enables it to have excellent corrosion resistance and long-term stability.
[0081] 4. The present invention proposes a method for preparing a composite coating of a metal bipolar plate of a fuel cell. The core steps of the preparation method are all carried out in a vacuum environment, which significantly reduces the emission of harmful gases. The vacuum environment effectively avoids the harmful chemical reactions that may occur when oxygen and other gases in the atmosphere come into contact with high-temperature materials, thereby reducing pollution to the environment; in a vacuum environment, the evaporation and deposition efficiency of the material is improved, which means that less material can be used to achieve the same coating effect. This efficiency improvement not only reduces the cost of raw materials, but also reduces the generation of waste, further reducing the impact on the environment.
[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
[0083] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0084] It should be noted that, in the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
Claims
1. A method for preparing a composite coating of a fuel cell metal bipolar plate, characterized in that: include: S1: pre-treat and clean the substrate; S2: depositing a metal primer layer and a transition layer on the surface of the substrate in sequence; S3: depositing an amorphous carbon surface layer on the surface of the transition layer by multi-arc ion plating.
2. The method according to claim 1, characterized in that: The step S1 includes: After the pretreatment of the substrate is completed, the substrate is placed in a vacuum chamber for plasma cleaning.
3. The method according to claim 1, characterized in that: The preprocessing comprises: Alkaline cleaning, rust removal and pure water rinsing.
4. The method according to claim 3, characterized in that: The alkali washing comprises: The substrate is immersed in a KOH solution with a mass percentage of 10%-15% and a temperature of 70° C.-90° C., and the substrate is ultrasonically cleaned for 5 min-20 min.
5. The method according to claim 3, characterized in that: The rust removal comprises: The substrate is immersed in a H2SO4 solution with a mass percentage of 10%-15% and a temperature of 70°C-90°C, and the substrate is ultrasonically cleaned for 5 minutes to 20 minutes.
6. The method according to claim 3, characterized in that: The pure water rinsing comprises: The substrate is placed in a cleaning tank and rinsed with ultrapure water for 5 minutes to 20 minutes.
7. The method according to claim 6, characterized in that: Also includes: The substrate rinsed with pure water is taken out, and the surface of the substrate is blown dry with compressed air at a temperature of 15° C.-30° C. and a pressure of 0.4 MPa-0.9 MPa.
8. The method according to claim 1, characterized in that: The step S1 further includes: After the substrate is subjected to any one of the steps of alkali washing, rust removal and pure water rinsing in the pretreatment, the surface of the substrate is sprayed and rinsed with pure water.
9. The method according to claim 2, characterized in that: The cleaning includes: The substrate is placed in the vacuum chamber, argon gas is introduced into the vacuum chamber, the pressure inside the vacuum chamber is 0.1Pa-1Pa, the temperature is 100°C-200°C, the applied voltage is -500V-800V, and the plasma cleaning time is 5min-30min.
10. The method according to claim 1, characterized in that: The step S2 includes: A metal base layer is deposited on the surface of the substrate by magnetron sputtering. After the metal base layer is completed, a transition layer is continuously deposited on the surface of the metal base layer by magnetron sputtering.
11. The method according to claim 10, characterized in that: The step S2 includes: The material of the metal primer layer includes titanium, vanadium, chromium, zirconium, niobium, molybdenum or tantalum.
12. The method according to claim 10, characterized in that: The step of depositing a metal base layer on the surface of the substrate by magnetron sputtering comprises: Argon gas is introduced into the vacuum chamber, the flow rate of argon gas is 200sccm-300sccm, the pressure is 0.1Pa-1Pa, the temperature is 100℃-200℃, the applied current is 2A-10A, and the deposition time is 10min-60min, until the thickness of the metal base layer reaches 97nm-155nm.
13. The method according to claim 10, characterized in that: The step S2 includes: The material of the transition layer includes titanium carbide, titanium nitride, titanium carbide nitride, niobium carbide or chromium carbide.
14. The method according to claim 10, characterized in that: The step of depositing a transition layer on the surface of the metal base layer by magnetron sputtering comprises: Argon and nitrogen are introduced into the vacuum chamber, the argon flow rate is 180sccm-280sccm, the pressure is 0.1Pa-1Pa, the temperature is 100℃-200℃, the applied current is 2A-10A, and the deposition time is 10min-60min, until the thickness of the transition layer reaches 48nm-103nm.
15. The method according to claim 2, characterized in that: The step S3 includes: The surface of the transition layer is deposited multiple times by multi-arc ion plating until the amorphous carbon surface layer reaches a required thickness.
16. The method according to claim 15, characterized in that: The step S3 includes: The material of the amorphous carbon surface layer is amorphous carbon.
17. The method according to claim 15, characterized in that: The method of performing multiple cycles of deposition on the surface of the transition layer by multi-arc ion plating until the amorphous carbon surface layer reaches a required thickness comprises: Argon gas is introduced into the vacuum chamber, the flow rate of argon gas is 50sccm-100sccm, the pressure is 0.1Pa-1Pa, the temperature is 100℃-150℃, the deposition time is 10min-20min, and the deposition is cycled 2-4 times until the thickness of the amorphous carbon surface layer reaches 147nm-255nm.
Citation Information
Patent Citations
Amorphous carbon coatings for fuel cell bipolar plates
CN101640276B
A graphite microcrystalline carbon coating for metal bipolar plates in fuel cells and its application
CN109037723B
Cited By
Multi-layer structure high-load-bearing self-lubricating wear-resistant coating and preparation method and application thereof
CN122147226A